DOES EMPLOYEE PERFORMANCE PERCEIVE WORKLOAD, STRESS, AND WORK ENVIRONMENT? THE MEDIATING FUNCTION OF JOB SATISFACTION - Fadila, MutiaNur; Sumastuti, Efriyani; Nastiti, Prianka Ratri (Journal of Management and Innovation Entrepreneurship (JMIE), 2025)
This study investigates the correlation of workload, work stress, and work environment on employee performance at Bank BRI KC Semarang Pattimura, with job satisfaction serving as a mediating variable. Data were acquired from 102 employees using a quantitative technique via questionnaires. Structural Equation Modeling (SEM) utilizing Partial Least Squares (PLS) in SmartPLS version 3 was utilized to assess validity, reliability, and hypothesis testing. The findings demonstrate that workload does not substantially influence employee performance, whether directly or via job satisfaction. Work-related stress substantially affects employee performance, both directly and indirectly through job satisfaction. Furthermore, the work environment positively influences job satisfaction and staff performance. Job happiness significantly contributes to improving employee performance. The findings underscore the significance of a supportive work environment and efficient stress management in enhancing job satisfaction and staff performance at Bank BRI KC Semarang Pattimura. Keywords: Workload, work stress, work environment, employee performance, job satisfaction.